Confronting bias in NGO research on modern slavery - Okyere, Samuel (Oxford University Press, 2018)
This chapter explores the extent to which efforts to attain more reliable, comprehensive data and knowledge on forced labour could be impeded by a lack of critical reflexivity in the use of mainstream conventional definitional and conceptual frameworks. Drawing on textual and discourse analysis of dissemination materials from a study of forced labour, the chapter makes three key contributions. First, it argues that uncritical reliance on mainstream discourses reinforces their dominance and forecloses alternative conceptualisations, interpretations and understandings of the nature, causes and effects of forced labour. Second, the absence of critical reflexivity gives rise to methodological issues that adversely affect research validity, reliability and quality. Third, crucial empirical findings could be distorted or ignored where they contradict conventional discourses, interpretations and frameworks adopted for the research.